Diferrocenylcyclopropenyl cations. Synthesis, structures, and some chemical properties - Klimova, Elena I.; Berestneva, Tatiana Klimova; Ortega, Simon Hernández; Iturbide, Daniel Méndez; Marquez, Alfonso García; García, Marcos Martínez (Journal of organometallic chemistry, 2005)
Synthesis of diferrocenylcyclopropenyl tetrafluoroborates with hetero-substituents in the three-membered ring, viz., ethoxy, trityloxy, ferrocenyl(phenyl)methoxy, N,N-diethylamino, piperidino, and morpholino, is described. The spatial structure of diferrocenyl(morpholino)cyclo-propenyl tetrafluoroborate was established based on the data from X-ray diffraction analysis. Under the action of potassium tert-butoxide, all the diferrocenylcyclopropenyl tetrafluoroborates undergo three-membered ring-opening with formation of the corresponding 2,3-diferrocenylacrylic acid derivatives. Synthesis of diferrocenylcyclopropenyl tetrafluoroborates with hetero-substituents in the three-membered ring, viz., ethoxy, trityloxy, ferrocenyl(phenyl)methoxy, N,N-diethylamino, piperidino, and morpholino, is described. The spatial structure of diferrocenyl(morpholino)cyclopropenyl tetrafluoroborate was established based on the data from X-ray diffraction analysis. Under the action of potassium tert-butoxide, all the diferrocenylcyclopropenyl tetrafluoroborates undergo three-membered ring-opening with formation of the corresponding 2,3-diferrocenylacrylic acid derivatives. A mechanism of the ring-opening is suggested.